Distribution and Community Structure of Coral Reefs In The West Coast Of Sumatra Indonesia - Rikoh Manogar Siringoringo; Tri Aryono Hadi; Ni Wayan Purnama Sari; Muhammad Abra; Munasik Munasik (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2019)
This paper assesses the distribution and community structure of coral species in six locations along the west coast of Sumatra, namely Mentawai, Bengkulu, Nias, Padang Pariaman, Simeulue, and Central Tapanuli. Data collected using Line Intercept Transect (LIT) method obtained from 55 sites at six locations. The ordination analysis by using PRIMER 7 software indicates the corals do not distributed evenly. In this case, almost all of the corals distributed mainly in Central Tapanuli and followed by Bengkulu, making it the most diverse corals location in the west coast. Mentawai and Padang Pariaman were less diverse and relatively similar as clustered together, but Padang Pariaman reefs had more Montipora and Pocillopora while Mentawai reefs is mainly featured by Pavona and Psammocora. Although Nias reefs clustered into two different clusters, the main reef features were Porites and Pavona. Simeulue reefs appeared characterized by Porites and Psammocora.  Porites known as a very common genus of coral and are found in the widest area of the world's coral reefs. The within-site species richness determined by using species accumulation curve. K-dominance curve showed that Bengkulu and Mentawai seemed to have the lowest cumulative abundance but then crossed over Central Tapanuli at the third most abundance species. There were 52 genera found from six locations, eight of them distributed in all locations. Approximately 90% of which were found in Central Tapanuli. There were no differences between live coral coverage within locations, yet Caswell’s neutral model showed that Mentawai and Bengkulu had more coral species than other locations, indicating that there were likely were less stress environmental conditions occurring in these two locations.